IMPROVING STUDENTS’ UNDERSTANDING OF IMPERATIVE SENTENCES BY USING TOTAL PHYSICAL RESPONSE METHOD - Ius Yusniah (English Didactic, 2019)
This research is aimed at knowing whether students’ understanding of imperative sentence can be improved by using Total Physical Response (TPR) method . This research uses Classroom Action Research (CAR). The Classroom Action Research design that is used in this research is Kurt Lewin’s Design; it consists of two cycles. Every cycle consists of four phases those are: planning, acting, observing, and reflecting. The subject of this research is the students of VII-D class of SMPN 1 Cimarga academic year 2010/2011. In collecting the data, this research uses observation, interview and test. The findings of the study are: first, related to the test result, using TPR method help students in understanding the imperative sentence and the students were able in answering the question about imperative sentence. It was proved by the pretest and the posttest in cycle 1 and cycle2 . Second, related to the observation result showed that the students were more active and interested in learning grammar especially imperative sentence in the classroom. Third, related to the interview result, it could be known that with using Total Physical Response method, the students’ understanding on imperative sentence has improved and also helped the teacher to find the appropriate strategy in teaching imperative sentece.